Introduction to the special issue - Adelaida López de Martínez (Studies in 20th & 21st Century Literature, 1996)
It is quite appropriate that Studies in Twentieth Century Literature should devote its 20th-anniversary special issue to the literature of Latin American women writers…
Keywords: Latin American women; women; women writers; feminism; voice; feminine perspective